Selection of primers for Cyt B gene to detect adulteration of meat products by PCR - Sergey Borovikov; Abirbekov Bisultan (World Scientific Reports, 2024)
The growth in food production is accompanied by an increase in food adulteration, especially in the meat and fish industries. Adulteration involves the addition of substandard ingredients or breaches of standards, thereby endangering health and misleading consumers. Losses from such activities range from $10 to $40 billion per year, and meat products are the most commonly targeted for adulteration due to their high cost and demand. Examples of such offences include replacing meat raw materials with vegetable or starch additives, which violates consumers' right to accurate information. The study aims to develop primers for the Cyt B gene in various animals and birds to detect adulteration of meat products by PCR. This method is the most accurate and reproducible for analysing species composition even in small quantities of raw materials. Modern modifications of PCR allow the analysis of both DNA and RNA, significantly expanding its capabilities. Mitochondrial DNA (mtDNA), especially the Cyt B gene, due to its high conservativeness, is widely used to determine the origin of meat, including processed products. Immunological methods such as agglutination reaction, precipitation reaction, diffusion precipitation reaction and ELISA are of limited use, especially in the case of small additions of foreign raw materials or in the case of heat treatment. However, ELISA is suitable for the analysis of raw semi-finished products.